POTENTIALS OF SOME PLANT-DERIVED FOODS IN THE MANAGEMENT OF DIABETES AND ASSOCIATED COMPLICATIONS - Ogunyinka, Bolajoko Idiat; Oyinloye, Babatunji Emmanuel; Adenowo, Abiola Fatimah; Kappo, Abidemi Paul (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background and Objective: Diabetes is an insidious as well as a debilitating metabolic disease with variety of causes that could lead to severe complications in multiple organs within the body system. There has been no documented scientific evidence as regards total cure of this complex chronic disease; therefore, it demands a lifelong management. This has necessitated the recent evaluation of several plant derived foods as costeffective alternatives in the management of diabetes and its associated complication. Materials and Methods: This review is based on integration of information from multi-databases after a comprehensive literature search on the various plant derived foods that have been reported to have shown a certain degree of amelioration in the management of diabetes and diabetic complications. Result and Discussion: Published reports suggest that oxidative stress primarily mediated by uncontrolled hyperglycemia play a pivotal role in the pathogenesis of diabetes and its associated complications. Therefore, various plant-derived foods are believed to delay, prevent or manage diabetes and its associated complications using different mechanisms which could be established through their potential to increase insulin sensitivity, free radicals scavenging abilities, hypolipidemic, hypoglycaemic, hypocholesterolemic, antioxidative, anti-inflammatory and inhibition of α-amylase and α-glucosidase activities. Conclusion: Based on the evidence presented in this review, plant-derived foods possess bioactive constituents believed to be rich in antioxidants and proteins which may be responsible for their mode of actions; we propose that Cucuma longa (curcumin), Garcinia kola (kolaviron), Telfairia occidentalis and Parkia biglobosa be explored in the management of diabetes and its associated complications due to their outstanding beneficial effects.